Countering the blow: Effectiveness of sertraline after traumatic brain injury. Issue 1 (January 2018) - Karsh, Andrea; Castelli, Gregory
Abstract : N/A: Jorge RE, Acion L, Burin DI, Robinson RG. Sertraline for preventing mood disorders following traumatic brain injury: a randomized clinical trial. JAMA Psychiatry . 2016; 73(10):1041–1047.